Genetic and Phenotypic Analysis of Meat Quality Traits in Buffalo Beef and Correlations to Carcass Composition - Sarubbi, F.; Palomba, R.; Baculo, R.; Auriemma, G.; Polimeno, F.; Maglione, G. (Journal of Buffalo Science, 2013)
Abstract: Meat quality traits in buffalo beef were examined and their genetic parameters and genetic correlations to carcass composition were estimated. Dissection was performed on 40 buffalo beef carcasses and all traits recorded for each animal, as well as the weight on muscle lungissimus dorsi (LD). The temperature and pH were recorded at 1 and 48h post-slaughter. Intramuscular fat, protein, dry matter, meat colour (redness, a*, yellowness b* and lightness L*) were recorded. Hereditability estimates ranged from 0.12 and 0.99 for dissection traits and 0.61 and 0.68 for meat quality traits, which was significant for all traits except for ultimate pH and b*. Genetic correlation with L* were negative for a* and high and positive for b*. Intramuscular fat was moderate to highly genetically correlated to the a*, b* and half hot carcass weight. The not significant genetic correlation found between several of the meat quality traits, and between meat quality traits and carcasses composition traits, suggests that the meat quality traits analyzed should be implemented into breeding programme with care since their full effect on the other traits under selection cannot be accurately estimated. For more accurate estimates, further studies that especially include a large number of records for colour meat measures are needed.